PENGARUH PENETAPAN HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI OLAHAN IKAN PATIN PADA GRAHA PRATAMA FISH DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR - Novia Ananda Putri; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of pricing and product quality on processed catfish at Graha Pratama Fish, Koto Mesjid Village, XIII District, Koto Kampar. This research method uses quantitative. The sample in this study used an accidental sampling technique of 100 respondents. This research was located at Graha Pratama Fish, Koto Mesjid Village, XII District, Koto Kampar. By using SPSS. The method of analysis of this study uses simple and multiple linear regression analysis by testing the validity and reliability tests. The results showed that partially the pricing variable was stated to have a significant effect on purchase intention of 57.4% and product quality had a significant effect on purchase intention of 31.9%. Then in the simultaneous test results it is known that the two variables, namely pricing (XI) and product quality (X2) have proven to have a significant effect on the dependent variable buying interest (Y) of 78.1%. Keywords: pricing, product quality and buying interest